2012
DOI: 10.1007/s00125-011-2427-7
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of C/EBP homologous protein (Chop) in C57Bl/6 mice dissociates obesity from insulin resistance

Abstract: Aims/hypothesis Endoplasmic reticulum (ER) stress has been implicated in the development of type 2 diabetes, via effects on obesity, insulin resistance and pancreatic beta cell health. C/EBP homologous protein (CHOP) is induced by ER stress and has a central role in apoptotic execution pathways triggered by ER stress. The aim of this study was to characterise the role of CHOP in obesity and insulin resistance.Methods Metabolic studies were performed in Chop −/− and wild-type C57Bl/6 mice, and included euglycae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 52 publications
4
48
0
1
Order By: Relevance
“…47 It has been reported that CHOP − / − mice on C57B1/J background preserve normal glucose tolerance and insulin sensitivity. 48 Moreover, CHOP-deficient mice did not develop albuminuria and ER stress-induced apoptosis in proximal tubular cells. 49 Caspase-12 is a member of the caspase family and is located in the ER.…”
Section: Discussionmentioning
confidence: 97%
“…47 It has been reported that CHOP − / − mice on C57B1/J background preserve normal glucose tolerance and insulin sensitivity. 48 Moreover, CHOP-deficient mice did not develop albuminuria and ER stress-induced apoptosis in proximal tubular cells. 49 Caspase-12 is a member of the caspase family and is located in the ER.…”
Section: Discussionmentioning
confidence: 97%
“…In line with this hypothesis, exposure of human pancreatic cells to the saturated NEFA palmitate induces ER stress, NF-κB activation and upregulation of IL-1β (also known as IL1B), TNF, IL-6 (also known as IL6), IL-8 (also known as IL8), CCL2 and CXCL1 expression [14]. Moreover, CHOP deletion decreases the induction of inflammation caused by excessive fat accumulation in liver and fat and, importantly, prevents insulin resistance [15].…”
Section: The Cross-talk Between the Upr And Inflammationmentioning
confidence: 98%
“…Studies of diabetes in Chop knockout mice are difficult to interpret, since these mice are often obese [15]. Preliminary observations in diabetes-prone NOD mice indicate that administration of a chemical chaperone, tauroursodeoxycholic acid, reduces diabetes incidence, improves survival and morphology of beta cells and reduces beta cell apoptosis [30].…”
Section: Upr Insulitis and Pancreatic Beta Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…CHOP contributes to rodent and human β-cell apoptosis and its expression is upregulated in islets from both T1D and T2D patients (Laybutt et al 2007, Cunha et al 2008. Besides its proapoptotic role, recent studies revealed a pro-inflammatory role for CHOP in different disease models, including myocardial inflammation (Miyazaki et al 2011), lung damage induced by LPS (Endo et al 2005), chemical hepatocarcinogenesis (DeZwaan-McCabe et al 2013), and high fat diet-induced diabetes (Maris et al 2012)…”
Section: Er Stress-induced Inflammation In Pancreatic β-Cells Er Strementioning
confidence: 99%